Author Correction: Noninvasive imaging of vascular permeability to predict the risk of rupture in abdominal aortic aneurysms using an albumin-binding probe - Lisa C. Adams (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.